탈북 청소년의 영어능력 신장을 위한 영화 활용 다중언어 프로그램 개발 및 적용 연구 - 장은영; Eun-young Jang (Multimedia-Assisted Language Learning, 2019)
This study aimed to develop a movie-based multilingual program for North Korean refugee adolescents and to investigate the effects of the program in enhancing the students’ multilingual awareness, as well as English learning. To create a multilingual context, the researcher used three foreign movies produced in English and Chinese as resources. Various types of multilingual worksheets, including translanguaging activities, watching and dictation, useful expressions, making connections, and writing a paragraph, were also developed in English, Chinese, and Korean. Analyses of various types of qualitative data such as curriculum and lesson plans, observations, interviews, and student products showed that this multilingual program had both advantages and limitations. Adopting multimedia and multilingualism to teach English to North Korean refugee adolescents was the most successful aspect of this program in that it helped them promote interest and self-esteem in their own multilingual abilities. Nevertheless, because the immediate problems that the students were facing, such as college application, family issues, and physical and mental illness, were hardly addressed in the program, it failed to make noticeable impact on and change in their motivation and English ability.